Anxiety and depressive symptoms are related to core symptoms, general health outcome, and medical comorbidities in eating disorders. (24th April 2019) - Martín, Josune; Arostegui, Inmaculada; Loroño, Ane; Padierna, Angel; Najera‐Zuloaga, Josu; Quintana, José M.
Abstract: Objective: The goal of this study is to identify potential factors that have a significant effect on anxiety and depression of patients with eating disorders (ED) using the beta‐binomial regression (BBR) approach on a broad sample of patients. Method: This cross‐sectional study involved 520 ED patients. The effect of sociodemographics, core symptoms, general health outcomes, and medical comorbidities in anxiety and depression were analysed jointly using the beta‐binomial mixed‐effects model. Results: Two hundred fifty‐five (49.4%) patients had anorexia nervosa, 173 (33.3%) patients had bulimia nervosa, and 92 (17.7%) had ED not otherwise specified. A high level of anxiety was associated, among other variables, with having a restrictive ED subtype as compared with purgative and binge ED subtypes ( β  = −0.2, p  < 0.001, OR  = 0.82 and β  = −0.16, p  < 0.03, OR  = 0.85, respectively), with having a high level of ED symptomatology or with living not alone ( β  = −0.23, p  = 0.002, OR  = 0.80). A high level of depression was associated, among other variables, with older age ( β  = 0.74, p  < 0.001, OR  = 2.1). Conclusions: The results of our study suggest that depressive and anxiety symptoms are related to ED symptoms, health status, ED subtype, medical comorbitidy, and educational level. In addition, another interesting finding is the inverse association between symptomatology of anxiety and living alone. Finally, BBR may be a useful approach in interpreting patient‐reported outcome as odds.